(untitled) (New York, 1969)
Contents: technology and industrial man; the machine and its critics; the prophets of the new; the existential revolution; technology and the rediscovery of politics...
Keywords: Công nghệ và nền văn minh,Xã hội đại chúng,Technology and civilization,Mass society